Analisis Efektifitas Pelaksanaan Program Penanggulangan Stunting Pada Kelurahan Jakasetia Kecamatan Bekasi Selatan Kota Bekasi Tahun 2022 - Zahran, Wahidin Septa; Irwansyah, Iwan; Setiawan, Dodi Rahmat; Ramdhan, Putra (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to identify and examine the problem of the high number of stunted children in Jakasetia Village, South Bekasi District, Bekasi City. This approach uses a qualitative approach and this type of research is descriptive research, data collection techniques in this study are using observation, interviews and documentation. The informants of this research include representatives of the UPTD Puskesmas, Village Representatives, Posyandu Cadres and Communities who have children under five years old. Based on the results of the study, it is known that the implementation of the Stunting Prevention Program in the Jakasetia Village area, South Bekasi Subdistrict, Bekasi City has been carried out well, especially in the aspects of Work Quantity, program objectives and implementer commitment. Human Resources are very sufficient in implementation, but not only human resources are sufficient, but financial support is also needed in the implementation of the Stunting Prevention Program to run optimally. in other aspects such as Quality of work, Timely and Achievement of Goals have reached their implementation standards, seen from the effect of the program being carried out. Obstacles or obstacles that affect the effectiveness of implementing this program are underprivileged families, low parental education, and lack of parental attention to children handling stunting